Human capital and macroeconomic growth: Austria and Germany 1960 - 1997. An update - Reinhard Koman; Dalia Marin (Institute for Advanced Studies (IHS), 1999)
In an influential paper Mankiw, Romer, and Weil (1992) argue that the evidence on the international disparity in per-capita income levels and growth rates is consistent with a standard Solow model, once it has been augmented to include human capital as an accumulable factor. In a study on Austria and Germany we augment the Solow model to allow for the accumulation of human capital. Based on a perpetual inventory procedure we construct measures of human capital stocks. We find that the time series evidence on Austria and Germany is not consistent with a human-capital-augmented Solow model. Factor accumulation appears to be less (and not more) able to account for the cross-country growth performance of Austria and Germany when human capital accumulation is included. Our results indicate that differences in technology are a driving factor in understanding cross-country growth between these two neighboring countries with similar political and institutional background.
Keywords: O1; O3; O4; 330; economic growth; total factor productivity; human capital; technical change; growth accounting